Auxiliary Differential Diagnosis of Schizophrenia and Phases of Bipolar Disorder Based on the Blood Serum Raman Spectra - ILDIZ, GÜLCE ÖĞRÜÇ; Bayari, Sevgi; Aksoy, Umut M.; Yorguner, Neşe; Bulut, Hüseyin; Yılmaz, Sultan S.; Halimoğlu, Gökhan; Kabuk, Hayrunnisa Nur; YAVUZ, GİZEM; Fausto, Rui (Wiley, 2020)
Schizophrenia (SZ) and bipolar disorder (BP) are severe psychiatric disorders that are characterized by an extensive spectrum of symptoms and affect approximately 2% of the world population. BP exhibits three well-distinct phases, which are classified as manic and depressive episodes and euthymic phase. These disorders are of difficult differential clinical diagnosis due to the similarity of their symptoms. Diagnostic approaches for SZ and BP are based on constructed patient interviews and subjective evaluations of clinical symptoms, and there are still no molecular-based auxiliary diagnostic tools to support the clinical diagnosis. In this study, an analytical model for auxiliary differential diagnosis of SZ and BP, based on the analysis of patients' blood serum Raman spectra, is developed, which is able to account for the different BP phases and can also differentiate SZ and BP patients from healthy individuals. The model is based on a hierarchical sequence of four two-class PLS-DA steps where the Raman spectra are theX-predictor variables. It is concluded that the full 400-3,100 cm(-1)Raman spectroscopic range is a sensitive probe for the disorders, thus working as a general spectroscopic biomarker for the illnesses. The proposed methodology is reliable, fast, cheap, essentially minimal-invasive, and might be implemented easily in the clinical environment.
Keywords: Bipolar Disorder; Chemometrics; Raman Spectroscopy; Schizophrenia